The role of pamali as an environmental conservation principle in the indigenous community of Kampung Naga and its implementation in supporting sustainable tourism development - Khosihan Aan; Wahyuni Sri; Utami Nindita Fajria; Nur Muhammad; Khaerani Rijal (E3S Web of Conferences)
This paper aims to answer the question of whether indigenous communities can sustain their environment amidst the growth of tourism in their regions to avoid potential future disasters especially in Kampung Naga. The researchers employed a descriptive qualitative research approach to explain the research findings. Data collection was conducted through indepth interviews with indigenous leaders of Kampung Naga and a literature review to enrich the findings. From the data analysis, it can be concluded that there are five types of Pamali practiced by the people of Kampung Naga which are Pamali asup ka leuweung larangan dan Pamali nuar tatangkalan di leuweung larangan, Pamali mun geus nuar tatangkalan tue dipelakan deui, Pamali ngala lauk ku racun/portas da menggunakan setrum, Pamali lamun tandur jeung panen lain dina bulana, and Pamali Panen dina poe apes. In practice, these local principles are also applied in the management of tourism and must be adhered to by tourists visiting Kampung Naga. The results of this research demonstrate that the Pamali principles can serve as tools for disaster mitigation practices while simultaneously supporting the implementation of sustainable tourism.